2015
DOI: 10.1055/s-0035-1560346
|View full text |Cite
|
Sign up to set email alerts
|

C–H Bond Transformations Leading to the Synthesis of Organic Functional Materials

Abstract: In this review, transition-metal-catalyzed or-mediated C-H transformations leading to the synthesis of organic functional materials, such as oligomers, polymers, and π-conjugated molecules, are summarized. 1 Introduction 2 Oligomers and Polymers 2.1 Synthesis of Oligomers and Polymers 2.2 Chemical Modification of Polymers 3 π-Conjugated Molecules 3.1 Indenes and Fluorenes 3.2 Acenes 3.3 Triphenylenes 3.4 Chemical Modification of Perylene Diimides 3.5 Nanographenes 3.6 Condensed Polycyclic π-Conjugated Molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 67 publications
0
15
0
1
Order By: Relevance
“…The authors confirmed the electrophilic nature of the active oxidizing species. The latter demonstrated high 3˝/2˝ratios (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), alcohol/ketone ratios > 5, and high stereospecificity in the oxidation of cis-1,2-dimethylcyclohexane [187]; kinetic studies revealed a sizable kinetic isotopic effect (k H /k D 4.5-4.7), indicating that that the H atom lies on the reaction coordinate and participates in the C-H bond breaking step. Altogether, the experimental data provided indirect evidence in favor of the participation of a high-valent (presumably oxometal(V) [188]) species, ruling out the contribution of a free-radical-driven oxidation pathway.…”
Section: New Types Of Ligands and Catalystsmentioning
confidence: 99%
“…The authors confirmed the electrophilic nature of the active oxidizing species. The latter demonstrated high 3˝/2˝ratios (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), alcohol/ketone ratios > 5, and high stereospecificity in the oxidation of cis-1,2-dimethylcyclohexane [187]; kinetic studies revealed a sizable kinetic isotopic effect (k H /k D 4.5-4.7), indicating that that the H atom lies on the reaction coordinate and participates in the C-H bond breaking step. Altogether, the experimental data provided indirect evidence in favor of the participation of a high-valent (presumably oxometal(V) [188]) species, ruling out the contribution of a free-radical-driven oxidation pathway.…”
Section: New Types Of Ligands and Catalystsmentioning
confidence: 99%
“…The UV-vis spectra of 7aa, 7bb, and 7ba were measured in chloroform, and the normalized UV-vis spectra are shown in Figure 1. These compounds showed similar peak patterns between 300 and 500 nm, and the π-π* transitions (p-band) for 7aa, 7bb, and 7ba were observed at 426 nm [11]. The peaks corresponding to n-π* transitions (α-band) were observed at 456-469 nm and were red-shifted with growing intensity as the number of hexyloxy groups increases.…”
Section: Resultsmentioning
confidence: 71%
“…However, in search of more efficient synthetic routes, C-H arylation reactions have been increasingly utilized in recent years for the rapid expansion of the aromatic frameworks [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some such reactions have been reported, and there have been several reviews, 24 including our own, 25 of such topics. In this section, I focus on the synthesis of π conjugated molecules bearing heteroatom(s) or a Lewis acid base interaction and on polymers.…”
Section: H Transformations Leading To the Synthesis Of Organic Funcmentioning
confidence: 97%